2018
DOI: 10.1007/s12105-018-0935-1
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Parotid (Mammary Analog) Secretory Carcinoma and Acinic Cell Carcinoma: Report of a Case

Abstract: Mammary analogue secretory carcinoma (MASC) is a recently described low-grade salivary gland malignancy with histologic, immunohistochemical and molecular similarities to secretory carcinoma of the breast, including a specific t(12;15)(p13;q25) resulting in an ETV6-NTRK3 gene fusion. Ultrasound and magnetic resonance imaging frequently document a macrocystic structure. The main differential diagnosis of secretory carcinoma is with low grade acinic cell carcinoma (AciCC). The two can be differentiated with immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Out of a total of 226 studies published between 2010 and 2023, identified at initial search and screened for retrieval, 112 1–3,6–114 articles were included in the study, with a total of 674 patients described in these articles. The identification and screening process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Out of a total of 226 studies published between 2010 and 2023, identified at initial search and screened for retrieval, 112 1–3,6–114 articles were included in the study, with a total of 674 patients described in these articles. The identification and screening process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, unlike AciCCs, SCSGs have no secretory zymogen cytoplasmic granules that undergo true positive periodic acid–Schiff reactions 17 . Additionally, the nuclei of SCSGs have prominent pseudo-inclusion bodies; however, SCSGs do not contain other cell types, such as serous, intermediate, and clear cells, which are commonly observed in AciCCs 18 . As for immunophenotypes, SCSGs can express various markers of breast secretory carcinomas, including mammaglobin, S-100 protein, STAT5A, MUC1, MUC4, GCDFP-15, CK7, CK8, CK18, CK19, and epithelial cell membrane proteins 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike ACCs, SCSGs have no secretory zymogen cytoplasmic granules that show true positive periodic acid-Schiff reactions [15]. The nuclei of SCSGs have prominent pseudo-inclusion bodies and SCSGs do not have the other cell types, such as serous, intermediate, and clear cells, that are seen in ACCs [16]. As to immunophenotypes, SCSGs can express various markers of breast secretory carcinomas, including mammaglobin, S-100 protein, STAT5A, MUC1, MUC4, GCDFP-15, as well as CK7, CK8, CK18, CK19, and epithelial cell membrane proteins [17].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of enhancement varied, mostly being uneven and marked (> 40 HU). However, a few tumors showed mild enhancement (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) or no obvious enhancement (< 10 HU). Most of the recurrences showed marked enhancement.…”
Section: Imaging Ndingsmentioning
confidence: 99%